In the scientific research of prof. dr. bekir chobanzadeh opinions on m. fuzūlīʼs language - PERVİN (Uluslararası Türk Lehçe Araştırmaları Dergisi)
As it is known, 2024 is the 530th anniversary of the birth of Muhammad Fuzuli, the great philosopher poet of the Turkic world and the East. M. Fuzuli, who gave excellent examples of classical Turkish poetry, further enriched the Azerbaijani language and raised it to the top of his period. One of the researchers who examined the literary personality of the genius poet, who made important contributions to the development of Turkish language and literature the famous Turkologist Bekir Chobanzadeh in his article titled “Fuzuli and His Place” who wrote in 1925, he talked about important issues related to the language of the poet, who has an important place in the history of Azerbaijani literary language. In the related article, B. Chobanzadeh draws attention especially to the vocabulary of M. Fuzûlî and gives information about the usage of both the words in the common Turkish vocabulary and Arabic and Persian quotations. B. Chobanzadeh also compared M. Fuzuli with other poets and emphasized that Fuzûlî not only based his poems on Turkish verbs, but also included many folk idioms and expressions that had not been used in literary works until his time. In addition, B. Chobanzadeh said, “Fuzuli is the only poet who made the intellectual class and the people cry with “Leyla and Majnun”, laugh with “Şikayetname” and cheer up with other ghazals with our greatest and most refined poets and our peasants who had never picked up a book for hundreds of years” and characterized Fuzuliʼs skillful use of the written language and the language of the people together as his greatest historical service. In his article, B. Chobanzadeh focused on an issue related to the language of the poet, which is still a matter of debate in Turkology to a certain extent: “Which dialect of Turkish did Fuzuliʼ write in?” B. Chobanzadeh came to the following conclusion in his analysis: “.... considers the language of Fuzuli, who wrote the following lines, closer to Azerbaijani dialect in terms of the Turkish part”. In the article, B. Chobanzadehʼs ideas were compared with the views of contemporary Turkologists, the discussions around the problem in question were mentioned in detail, and these were essentially determined that the idea that Azerbaijani language is at the center of gravity of the language of Fuzuliʼs works is more defended in researches.